Time Series Analysis of the Implementation of Child Support Enforcement Policies in Federal Region V States - Dubey, Sumati (1997)
This study examines the impact legislation, such as the Family Support Act of 1988, Child Support Recovery Act of 1992 and Ted Weiss Child Support Enforcement Act of 1992 had on child support enforcement in Federal Region V states (Illinois, Indiana, Michigan, Minnesota, Ohio, and Wisconsin). These pieces of legislation authorize coercive means to force noncustodial parents to meet their child support obligations. Child support is the money noncustodial parents are obligated to pay for the support of their children on a monthly basis. Child support laws have been enacted to increase the number of noncustodial parents located, paternities established, child support orders issued, and child support payments. Social and economic factors that help to explain state variations in child support collections are also analyzed. Time series analysis was applied to secondary data collected from 1984-1994. The data was collapsed into two periods 1984-1988 and 1989-1994 in order to determine if legislation enacted after 1988 had an effect on child support enforcement in Federal Region V. The results from this study indicate that certain variables had the greatest impact on child support enforcement in each state in Federal Region V The findings from this study provide beneficial strategies which may enhance current child support enforcement practices